SELF-EFFICACY OF JUNIOR HIGH SCHOOL STUDENTS IN ONLINE LEARNING - Sri Ningsih; Sugiman Sugiman (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The purpose of this study was to see how self-efficacy of students towards the learning process online amid the Covid-19 outbreak. This research is a descriptive study that describes self-efficacy based on the dimensions that exist in self-efficacy and is summarized and used as a measurement tool or instrument, namely the level (magnitude) associated with task difficulties, strength related to the effort made by students, and energy-related to space. the scope of student beliefs. The instrument used was a non-test in the form of a questionnaire self-efficacy consisting of 30 statements with 4 choices and 616 respondents. The result is that the dimensions of the level of Indonesian SMP / MTs students are in the medium category with a percentage of 55.04%, which means that when students are faced with difficult tasks during learning online, students can overcome them. The dimension strength is in the medium category with a percentage of 56.82%, this shows that the efforts and resilience of Indonesian SMP / MTs students in doing assignments in learning are online quite persistent and do not give up easily. The dimension generality is in the medium category with a percentage of 45.94%, which means that Indonesian SMP / MTs students' confidence in completing different tasks is quite good. In general, the self-efficacy of Indonesian SMP / MTs students in learning online is quite good.